Phylogeography of the purple snail Plicopurpura pansa along the Mexican Pacific coast - Felipe J López-Chávez; Omar Chassin-Noria; Patricia Ríos-Chávez; Víctor Rocha-Ramírez; Rodrigo Macip-Ríos; Ken Oyama (Ciencias Marinas, 2016)
The purple snail Plicopurpura pansa is a common member of the rocky intertidal community of the Tropical Eastern Pacific. It has a free-living larva that is dispersed by marine currents. We analyzed the demographic (historic), genetic, and phylogeographic structure of P. pansa using a fragment of the cytochrome b gene (687 bp). Data were analyzed by analysis of molecular variance, nested clade analysis (NCA), and a mismatch distribution analysis under the expanding population hypothesis. A total of 219 organisms were collected from 16 localities along the Mexican Pacific coast and one in Costa Rica. We obtained a total of 92 haplotypes. Genetic differences among Mexican populations were low. The Clarión Island population was significantly different from 6 of the Mexican populations studied. This result was attributed to the fact that Clarión is an oceanic island and the currents veer offshore most of the year. Haplotype network and mismatch distribution analyses indicated that the Mexican populations are undergoing expansion. The NCA confirmed a contiguous range expansion of haplotypes and this result may be related to the time that larvae spend in marine currents and to the effect of natural barriers, such as gyres, in Central America and the Isthmus of Tehuantepec.